Chloride Transport Performance of Basalt-Polypropylene Fiber Reinforced Concrete under Drying-Wetting Cycles - Li Su; Ditao Niu; Daguan Huang; Qiang Fu (Advances in Materials Science and Engineering)
This study investigated the chloride transport performance of basalt-polypropylene fiber reinforced concrete (BPFRC) subjected to drying-wetting cycles. The effects of the strength grade, basalt fiber (BF), polypropylene fiber (PF), and hybrid BF-PF on the pore solution pH, chloride concentration distribution, chloride peak concentration (Cmax), and apparent chloride diffusion coefficient (Da) of the BPFRC were analyzed, and a multifactor model of Da was established. Moreover, the microstructures of BPFRC were studied to explore the effect of fibers on chloride transport performance of concrete in terms of theoretical pore volume, fiber-matrix interface, fiber bonding properties, and corrosion morphology. The results showed that the chloride concentration of the BPFRC increased and the pore solution pH of the BPFRC decreased with the increase in the exposure time. The chloride concentration and Da of the BPFRC decreased with the increase in the strength grade. At a fiber volume content of 0.1%, the addition of BF and PF reduced the chloride concentration and Da of the BPFRC; at a fiber volume content of 0.2%, the addition of hybrid BF-PF increased the chloride concentration and Da of the concrete. The chloride peak concentration appeared at the depth of 2 mm inside the concrete, and the change of the chloride peak concentration with exposure time followed the power function model. The theoretical pore volume of the BPFRC specimens decreased initially and then increased with the increase in the exposure time. FE-SEM observed that the bonding property between BF and matrix was better than that of PF, which could effectively control the development of microcracks.